Reversible Inhibition of Iron Oxide Nanozyme by Guanidine Chloride - Mo, Wei-chuan; Yu, Jia; Gao, Li-zeng; Liu, Ying; Wei, Yan; He, Rong-qiao (Frontiers in Chemistry, 2020)
Nanozymes have been widely applied in bio-assays in the field of biotechnology and biomedicines. However, the physicochemical basis of nanozyme catalytic activity remains elusive. To test whether nanozymes exhibit an inactivation effect similar to that of natural enzymes, we used guanidine chloride (GuHCl) to disturb the iron oxide nanozyme (IONzyme) and observed that GuHCl induced IONzyme aggregation and that the peroxidase-like activity of IONzyme significantly decreased in the presence of GuHCl. However, the aggregation appeared to be unrelated to the quick process of inactivation, as GuHCl acted as a reversible inhibitor of IONzyme instead of a solo denaturant. Inhibition kinetic analysis showed that GuHCl binds to IONzyme competitively with H2O2 but non-competitively with tetramethylbenzidine. In addition, electron spin resonance spectroscopy showed that increasing GuHCl level of GuHCl induced a correlated pattern of changes in the activity and the state of the unpaired electrons of the IONzymes. This result indicates that GuHCl probably directly interacts with the iron atoms of IONzyme and affects the electron density of iron, which may then induce IONzyme inactivation. These findings not only contribute to understanding the essence of nanozyme catalytic activity but also suggest a practically feasible method to regulate the catalytic activity of IONzyme.